Breast and Cervical Cancer Screening Among Rural Midwestern Latina Migrant and Seasonal Farmworkers - Sheila F. Castañeda; Rene Perez Rosenbaum; Patricia Gonzalez; Jessica T. Holscher (SAGE Publishing, 2012)
Background : While cancer control and prevention efforts are well documented, limited information on this topic exists for Latina farmworkers in the rural Midwest. This study sought to examine correlates of breast cancer and cervical cancer screening practices of English- and Spanish-speaking Latina farmworkers in Michigan. Methods : Survey and anthropometric data were collected from a community-based cross-sectional sample of 173 Latina agricultural laborers in Michigan. Psychosocial-cultural and socioeconomic variables were examined as predictors of mammography and Papanicolaou screening. Findings : Results showed that individual characteristics that were significantly associated with having a Papanicolaou examination in the last 12 months included having higher language-based acculturation (odds ratio = 3.81), having ever done a breast self-examination (odds ratio = 2.82), and having health insurance (odds ratio = 5.58). Conclusions : Acculturation, insurance, and performance of breast self-examination were key correlates of recent cervical cancer screening among Midwest Latina farmworkers. Findings suggest that education and targeted outreach strategies for Spanish-speaking Latina farmworker women in rural settings are urgently needed.